Lilla’s Heritage. Cultural Sketches of the Vay Branch in Hungary - Lili Veronika Békéssy (Arti Musices)
The Vay family, from which Dora Pejačević’s mother Erzsébet (Lilla) hailed, played a significant role in shaping the formative years of the young composer, Dora. There is however, little research on that topic regarding the cultural heritage Dora inherited. The lineage of this family, though only partially documented from a musicological point of view, unveils a significant impact on Dora’s abilities and sensitivities by diligently scrutinizing press and archival records from that era. These records highlight a legacy of academic, political, and artistic achievements associated with her background. Lilla Vay was involved in various cultural events and dedicated much of her time to representing causes promoting the interests of Hungarian literature and art, in addition to her social and philanthropic activities. Meanwhile she was active as a Liebhaber performer, too. Lilla Vay placed significant importance on providing her children with musical education, in harmony with the aristocratic upbringing’s emphasis on arts education. Her children were engaged in chamber music performances at various social gatherings, showcasing their musical talents on numerous occasions. Károly Noseda, the initial music instructor of the Pejačević children, had a deep personal bond with the church on Servita Square, where Lilla may have attended worship services. Noseda later held a considerable position in musical life, functioning as the choirmaster at the Royal Opera House in Budapest and as a director at the National Conservatory. The influence of Lilla Vay, along with the musical background of their family, probably exerted a substantial impact on the musical inclinations of young Dora Pejačević and her siblings. It is evident that Dora’s musical performances received frequent mentions in the press; however, she occupied a comparatively minor position in the texts when compared to her mother, Lilla.